ҚАРАҚАЛПАҚ ӘДЕБИЯТЫ ҲӘМ ШЫҒЫС ПОЭЗИЯСЫНЫҢ ЖАНРЛЫҚ ӨЗГЕШЕЛИГИ - Давлетов, Б. (ILIM hám JÁMIYET, 2018)
The article deals with the genre of byte in the creation of the poets of Karakalpak literature of the XIX –th century Ajiniyaz and Kazi Mavlik on the basis of the literary and other materials.